The Effect of Product, Price, Place and Promotion on Customer Satisfaction: The Case of PT Palembang Agro Sejahtera South Sumatera - Pebrianto, Dedy; Moelyati, Trisniarty Adjeng; Nurrahmi, Maftuhah (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine 1) The Influence of Product, Price, Place and Promotion on Customer Satisfaction at PT Palembang Agro Sejahterah in South Sumatra, 2) The Influence of Product on customer satisfaction at PT Palembang Agro Sejahterah in South Sumatra, 3) The Influence of Price on Customer Satisfaction at PT Palembang Agro Sejahterah in South Sumatra, 4) The Influence of Place on Customer Satisfaction at PT Palembang Agro Sejahterah in South Sumatra, 5) The Influence of Promotion on Customer Satisfaction at PT Palembang Agro Sejahterah in South Sumatra. This type of research is quantitative descriptive. The variables used by researchers include product, price, place, promotion, and customer satisfaction. The sample in this study consisted of farmers who had shopped for PT Palembang Agro Sejahterah products, totaling 90 people selected by cluster random sampling. The data used in this study were primary data collected using a questionnaire. The data analysis technique used was multiple linear regression, as implemented in the SPSS Program Application. The results of this study indicate that (1) product, price, place, and promotion have a significant effect on customer satisfaction, (2) product has a significant effect on customer satisfaction, (3) price has a significant effect on customer satisfaction, (4) place has a significant effect on customer satisfaction. (5) promotion has a significant effect on customer satisfaction.